Quantum Cascade Lasers: Tunability of the Free‐Spectral Range by Microwave Injection into a Mid‐Infrared Quantum Cascade Laser (Laser Photonics Rev. 14(5)/2020). Issue 5 (7th May 2020) - Rodriguez, Etienne; Mottaghizadeh, Alireza; Gacemi, Djamal; Jeannin, Mathieu; Asghari, Zahra; Vasanelli, Angela; Todorov, Yanko; Wang, Qi Jie; Sirtori, Carlo
Abstract : The extremely short lifetime of optical transitions between electronic states in the conduction band (intersubband transitions) favors an ultrafast gain dynamic and the generation of optical combs. In article number 1900389, Etienne Rodriguez, Qi Jie Wang, Carlo Sirtori, and co‐workers show that by modulating the laser at its round‐trip frequency, it is possible to generate new longitudinal modes in the spectrum and to tune the free‐spectral‐range while keeping a comb‐like regime.